2017
DOI: 10.3390/vision1040023
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Studies on The Dynamics of Luminance Adaptation in the Mouse Retina

Abstract: To date, most studies involving in vivo electroretinography in mice are performed on steady state adapted animals. In this study, we focused on the dynamics of adaptation to high and low light levels in the mouse retina. Two flash electroretinogram (ERG) protocols and one flicker ERG protocol were employed. In the two flash ERG protocols, the animals were adapted to either 25 or 40 cd/m 2 white light and ERGs were recorded for up to 15 min of adaptation. Afterwards, flash ERGs were recorded for up to 45 min of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…In a previous study, we showed that it takes at least 30 minutes for the parameters of flash-and flicker-ERG to reach a steady state to low luminances. 21 The present study suggests an even longer time period for rods to fully adapt. DeMarco et al 22 found the retinal sensitivity in wild-type mice to increase over a time course of about 40 minutes during dark adaptation after previous light adaptation to 2.4 log cd/m 2 (»250 cd/m 2 ) for 10 minutes and was even much more delayed in Gnat2 cplf3 mice lacking functional cones.…”
Section: Rod-driven Responses Adapt Over Several Minutes To Low Lightmentioning
confidence: 54%
See 4 more Smart Citations
“…In a previous study, we showed that it takes at least 30 minutes for the parameters of flash-and flicker-ERG to reach a steady state to low luminances. 21 The present study suggests an even longer time period for rods to fully adapt. DeMarco et al 22 found the retinal sensitivity in wild-type mice to increase over a time course of about 40 minutes during dark adaptation after previous light adaptation to 2.4 log cd/m 2 (»250 cd/m 2 ) for 10 minutes and was even much more delayed in Gnat2 cplf3 mice lacking functional cones.…”
Section: Rod-driven Responses Adapt Over Several Minutes To Low Lightmentioning
confidence: 54%
“…We previously described that this adaptation time is sufficient to reach a steady state. 21 After the baseline measurement, the mean luminance was increased to 8.8 cd/m 2 mean luminance for 11 minutes (high light level), and the responses were recorded every 2 minutes, with the first recording starting directly after the mean luminance was increased. In total, six recordings were performed.…”
Section: Experimental Protocolsmentioning
confidence: 99%
See 3 more Smart Citations